2021
DOI: 10.1111/jocs.15563
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the aortic arch in adult general population and their association with thoracic aortic aneurysm disease

Abstract: Background: Query a single institution computed tomography (CT) database to assess the prevalence of aortic arch anomalies in general adult population and their potential association with thoracic aortopathies. Methods: CT chest scan reports of patients aged 50-85 years old performed for any indication at a single health system between 2013 and 2016 were included in the analysis. Characteristics of patients with and without aortic arch anomalies were compared by t test and Fisher exact tests. Logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Yousef et al 1 confirm the findings of previous studies in which ARSA in adult patients is frequently complicated by aortic arch aneurysm or by aortic dissection, especially when the origin of this artery is involved by an aneurysmal dilatation, as in Kommerell diverticulum (KD). 2,3 Despite these severe complications, there is no clear consensus on the best management of patients with KD and specific guidelines on surveillance and treatment are lacking.…”
Section: Tailored Management In Aortic Arch Anomaliessupporting
confidence: 82%
See 1 more Smart Citation
“…Yousef et al 1 confirm the findings of previous studies in which ARSA in adult patients is frequently complicated by aortic arch aneurysm or by aortic dissection, especially when the origin of this artery is involved by an aneurysmal dilatation, as in Kommerell diverticulum (KD). 2,3 Despite these severe complications, there is no clear consensus on the best management of patients with KD and specific guidelines on surveillance and treatment are lacking.…”
Section: Tailored Management In Aortic Arch Anomaliessupporting
confidence: 82%
“…To the Editor We read with great interest the article by Yousef et al 1 reporting the prevalence of aortic arch anomalies in the adult population and their association with thoracic aortic aneurysms (TAA). The authors underlined the importance of a tailored management strategy in patients with aortic arch anomalies, particularly in cases of aberrant right subclavian artery (ARSA), since this subset is at high risk to develop TAA.…”
Section: Tailored Management In Aortic Arch Anomaliesmentioning
confidence: 99%
“…Variant aortic arch anatomy has been found to be significantly associated with TAA in several single-center retrospective observational series, 1 with 33% of patients with right-sided aortic arch having concomitant TAA. 2 Left-sided aortic arch with aberrant right subclavian artery was also significantly associated with TAD but only occurred in 2% to 8% of those patients. 1 Consequently, if the imaging study that detected the ASCA did not include imaging of the thoracic aorta, then a dedicated CT or MRI to evaluate for an associated aortic aneurysm is reasonable.…”
Section: Other Aortic Conditionsmentioning
confidence: 90%
“…Repair of Kommerell’s diverticulum has been suggested when the orifice diameter is >3 cm or the combined diameter of the diverticulum and adjacent descending thoracic aorta is >5.0 cm. 3,4,7…”
Section: Other Aortic Conditionsmentioning
confidence: 99%
“…A systematic review and meta-analysis published in 2020 by Marrocco-Trischitta et al [8], including 8 studies enrolling 11,381 subjects, found the rate of thoracic aortic disease among CILCA arch patients to be higher (41.5%, 95% CI 28.1-56.4) than the rate among patients with standard arch configuration (34.0%, 20.1-51.4), with an odds ratio of 1.4 and an overall significant association between CILCA arch and thoracic aortic disease. More recently, Yousef et al [38] investigated the prevalence of aortic arch variants in the adult population and their association with thoracic aortic aneurysm disease. On a single-institution large database of 21,336 CT scans, they found 603 (2.8%) described arch anomalies, 354 of them (58.7%) with the bovine arch being the most common diagnosis.…”
Section: Discussionmentioning
confidence: 99%